DABCO-Promoted [3+2] Annulation for Efficient Synthesis of 1,2,5-Triaryl-1H-imidazoles from Substituted β-Nitrostyrenes and N-Arylbenzimidamides - Zhang, Yue; Wan, Xinyi; Gan, Jianbo; Wang, Cunde (Synthesis, 2021)
An efficient approach to the synthesis of 1,2,5-trisubstituted imidazole derivatives was investigated via a DABCO-promoted formal [3+2]-annulation reaction of substituted N-arylbenzimidamides and substituted β-nitrostyrenes. The annulation reaction is implemented easily to afford the corresponding products in moderate to good yields with excellent regioselectivity.
Keywords: 1,2,5-trisubstituted imidazoles; [3+2] annulation; cycloaddition; N-arylbenzimidamides; β-nitrostyrenes